Liberar ou não liberar, eis a questão: estudo de caso de ensino em administração pública - Cavalcanti, Cláudia Uchôa (2015)
The Case Study is the execution of work on the market of a municipality and the release of the administrative process for conducting bidding process. Presents the conflict between the Secretary of Works and the undersecretary of planning and budget in the conduct of the determinations of the chief executive. The newly elected Mayor decided to initiate reform with expansion of the popular market in the city of Três Barras. For this purpose, asked the Works Secretary architectural design with initial forecast costs could initiate the bidding process immediately, so as not to delay the opening of the new market by the first year in office. The undersecretary of planning and budge must make the decision to release or not the process as there is the need for care of the technical and legal requirements it considered necessary. This case can be work within the following topic: Planning and Budget Management